Implementation of the Project Based Learning For Improve Learning Skills in Ornamental Fish Cultivation Technology Course - Affandi, Rangga Idris; Setyono, Bagus Dwi Hari; Junaidi, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Learning at the higher education level needs special attention. The learning strategies used by teachers also need to be developed. One learning model that can be used in higher education is project-based learning. The aim of this study is implementing a new learning model using a project-based learning because it's able to increase students' understanding and practical skills in ornamental fish cultivation course. This research was carried out at the Aquaculture Study Program, Faculty of Agriculture, University of Mataram. The population in this study were students of the aquaculture study program. This research was conducted in the odd semester of the 2023/2024 academic year. This type of research is descriptive research, with a qualitative approach. The implementation of project-based learning in the ornamental fish cultivation technology course has several stages: problem recognition by asking students a question regarding the topic of ornamental fish cultivation that is currently occurring in society; plan a project from the existing topic; continue with preparing an activity schedule; project implementation and supervision; assessment and evaluation. The conclusion is that there is a significant influence from the application of the Project Based Learning on students' learning understanding and practical skills in ornamental fish cultivation technology course.